Visitor Satisfaction of Sunan Bonang Religious Tourism - Norita Vibriyanto; Yufita Listiana; Rian Abrori (ProBisnis : Jurnal Manajemen, 2023)
Sunan Bonang is one of Indonesia's religious tourism. The existence of Sunan Bonang religious tourism has economic benefits, especially for the surrounding community. This benefit can be lost when the interest of visitors to travel decreases, therefore it is important to know the level of visitor satisfaction to increase visitors of Sunan Bonang's religious tourism. The results of this research on Sunan Bonang visitor satisfaction seen from 4 aspects, are services, infrastructure facilities, security and self-reflection. Its show that visitor satisfaction is good category. So we need a strategy to increase visitor satisfaction for the number of visits increases.